2021
DOI: 10.1002/adfm.202107119
|View full text |Cite
|
Sign up to set email alerts
|

High‐Purity Monochiral Carbon Nanotubes with a 1.2 nm Diameter for High‐Performance Field‐Effect Transistors

Abstract: Monochiral single-walled carbon nanotubes (SWCNTs) are promising materials with potential applications in 3D integrated circuits and optoelectronic hybrid circuits. However, the purity and device performance of monochiral SWCNTs are still far lower than expected. Here, the authors demonstrate that specific monochiral SWCNTs can be wrapped by conjugated polymers containing pyridine units, and the supramolecular assemblies show surprising suspension stability even after high-intensity ultracentrifugation. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…Similar phenomena were also reported in PFO-BT enriched (10,5) from HiPCO tubes; after 1-month storage, (10,5) was retained in solution in a higher content, while the other species, (9,4), had reaggregated and was removed by recentrifugation . Such differences in ( n , m ) stability in solution likely originate from differences in polymer wrapping capability toward specific chirality, which can be employed to improve chiral purity by slow filtration, long-term storage, or ultracentrifugation . Meanwhile, significant yield loss (half or greater) was observed, which depends on specific chiralities and techniques employed.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Similar phenomena were also reported in PFO-BT enriched (10,5) from HiPCO tubes; after 1-month storage, (10,5) was retained in solution in a higher content, while the other species, (9,4), had reaggregated and was removed by recentrifugation . Such differences in ( n , m ) stability in solution likely originate from differences in polymer wrapping capability toward specific chirality, which can be employed to improve chiral purity by slow filtration, long-term storage, or ultracentrifugation . Meanwhile, significant yield loss (half or greater) was observed, which depends on specific chiralities and techniques employed.…”
Section: Resultssupporting
confidence: 71%
“…Poly­[(9,9-dioctylfluorenyl-2,7-diyl)- co -1,4-benzo-{2,1′-3}-thiadiazole] (PFO-BT) enriched (10,5) from HiPCO SWCNTs (purity ca. 53–60%). , Poly­(9,9-dioctylfluorene-2,7-diyl- alt -pyridine-2,6-diyl) (PFO-Py2,6) was recently reported to enrich (10,8) from HiPCO SWCNTs, and the purity reached 92.3% after ultracentrifugation (650 000 g for 6 h) . PFH-A enriched high purity (9,8) from SWCNTs produced by CoSO 4 /SiO 2 catalyst (catalyst controlled growth of (9,8)) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52][53][54][55] Most recently, Li et al demonstrated the semiconducting separation of conjugated polymer-wrapped SWCNTs larger than 1 nm, followed by ultracentrifugation and stepwise extraction processing to yield monochiral (10,8) and (12,5) SWCNTs with diameters larger than 1 nm. 56 The discovery of a one-pot sorting strategy using a conjugated polymer extraction technique with specic chirality selectivity is a critical issue in the current eld.…”
Section: Introductionmentioning
confidence: 99%
“…1,8 Many techniques have been developed to eliminate the drawbacks of metallic nanotubes, [9][10][11][12][13][14] for instance, solution-processed techniques, such as density gradient ultracentrifugation (DGU) 15 and gel ltration technique, 16 are representative to separate metallic and semiconducting CNTs effectively. Nowadays, the purity of semiconducting CNTs above 99% have been achieved with the help of state-of-the-art polymer-sorted DGU, [17][18][19][20] and the resultant CNT TFTs exhibit on/off ratio around 10 8 with mobility of 297 cm 2 V À1 s À1 . 17 But the scalability of solutionprocessed CNT lm should be an inevitable issue for their applications in large-scale exible electronic devices compared with the meter-scale and roll-to-roll as-grown CNT lms, 21 even though the fabrication of CNT TFTs is wafer-scale across 200 mm silicon substrates right now.…”
Section: Introductionmentioning
confidence: 99%